2021
DOI: 10.3390/pharmaceutics13020200
|View full text |Cite
|
Sign up to set email alerts
|

Topical and Systemic Formulation Options for Cutaneous T Cell Lymphomas

Abstract: Although various anti-cutaneous T-cell lymphoma (CTCL) therapies are available for clinical use, appropriate chemotherapy lines for the treatment of CTCLs have yet to be established. Therefore, to date, various clinical trials for the treatment of advanced CTCLs are ongoing. In this review, we evaluate the therapeutic options that are available in clinical practice for treatment of early- and advanced-stage CTCLs (targeted therapies, histone deacetylase (HDAC) inhibitors, retinoids, interferons, cytotoxic drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 78 publications
(204 reference statements)
0
20
0
1
Order By: Relevance
“…Since a previous report suggested that multiagent chemotherapy such as CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) had no indications in CTCL as a first-line therapy because of its poor efficacy [ 4 ], these chemotherapy protocols were not recommended for the treatment of PCALCL. Another possible therapy for PCALCL is brentuximab vedotin (BV), which is an anti-CD30 monoclonal antibody conjugated to monomethyl auristatin E via a protease-cleavable linker; it is used for the treatment of CD30+ lymphomas such as PCALCL [ 5 ], but BV is not permitted by the Pharmaceuticals and Medical Devices Agency (PMDA) in Japan for the treatment of PCALCL. For the above reasons, radiation therapy with oral administration of bexarotene, which was discontinued due to severe adverse events (hypertriglyceridemia), was selected as first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since a previous report suggested that multiagent chemotherapy such as CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) had no indications in CTCL as a first-line therapy because of its poor efficacy [ 4 ], these chemotherapy protocols were not recommended for the treatment of PCALCL. Another possible therapy for PCALCL is brentuximab vedotin (BV), which is an anti-CD30 monoclonal antibody conjugated to monomethyl auristatin E via a protease-cleavable linker; it is used for the treatment of CD30+ lymphomas such as PCALCL [ 5 ], but BV is not permitted by the Pharmaceuticals and Medical Devices Agency (PMDA) in Japan for the treatment of PCALCL. For the above reasons, radiation therapy with oral administration of bexarotene, which was discontinued due to severe adverse events (hypertriglyceridemia), was selected as first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Bexarotene is a third-generation retinoid X receptor-selective retinoid that has been approved for use in the treatment of CTCLs [2, 3, 5-8]. Since the objective response rate of bexarotene is relatively high, with no racial differences, bexarotene can be administered to patients with phototherapy-resistant early CTCL as one of the first-line therapies in real-world clinical practice [2, 3].…”
Section: Discussionmentioning
confidence: 99%
“…Since the objective response rate of bexarotene is relatively high, with no racial differences, bexarotene can be administered to patients with phototherapy-resistant early CTCL as one of the first-line therapies in real-world clinical practice [2, 3]. In addition, several clinical trials and multicenter, retrospective studies suggested that bexarotene causes characteristic adverse events such as hypothyroidism, hyperlipidemia, and leukopenia [2, 3, 5-8]. Although various adverse events have been reported, there have been no reports of drug eruptions caused by bexarotene, even in real-world clinical experience data from post-marketing surveillance [4].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, since CCL17 and CCL22 are ligands of CCR4, the major chemokine receptor expressed in CTCL cells, the production of these chemokines from TAMs could result in tumor formation in mycosis fungoides in the tumor stage. These findings suggest the necessity of different therapeutic approaches for the patch and tumor stages of mycosis fungoides [ 7 ].…”
Section: Profiles Of Tumor-infiltrating Leukocytes Determine the Char...mentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs), such as anti-programmed cell death 1 (PD1) antibodies (Abs) and anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA4) Abs, have been widely administered for not only advanced melanoma [ 1 , 2 ], but also various non-melanoma skin cancers [ 3 ] such as advanced cutaneous squamous cell carcinoma (cSCC) [ 4 ], advanced basal cell carcinoma (BCC) [ 5 ], cutaneous T cell lymphomas (CTCLs) [ 6 , 7 ], and cutaneous angiosarcoma (CAS) [ 8 ]. The efficacy of ICIs is often higher for these than for melanoma [ 4 ].…”
Section: Introductionmentioning
confidence: 99%